1981
DOI: 10.1159/000238024
|View full text |Cite
|
Sign up to set email alerts
|

Comparative in vitro Activity of 8 Cephalosporins on 109 Strains of <i>Neisseria gonorrhoeae</i> and 60 Strains of <i>Neisseria meningitidi</i><i>s</i>

Abstract: The in vitro activity of 8 cephalosporins – cephalothin, cefamandole, cefoxitin, cefuroxime, cefotaxime, cefoperazone, moxalactam and ceftriaxone (Rocephin®) was studied on 109 strains of Neisseria gonorrhoeae and 60 strains of Neisseria meningitidis, isolated from pathological material. Determination of the MICs of these antibiotics by an agar dilution method shows that on N. gonorrhoeae ceftriaxone (geometric mean of the MICs: 0.0008 μg/ml) is the most active, followed by cefotaxime (0.001 μg/ml); cefoperazo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…Preliminary studies suggest that a single dose of between 50 and 125 mg of ceftriaxone per kg is adequate for the treatment of uncomplicated gonorrhea (4). In vitro susceptibility tests have shown that the minimal inhibitory concentration of ceftriaxone for P-lactamase-producing N. gonorrhoeae is approximately 0.01 ,ug/ml (10). These observations and the results of the current study suggest that ceftriaxone would be effective as a single-dose regimen against mixed infections with T. pallidum and ,1-lactamase-positive N. gonorrhoeae.…”
Section: Discussionsupporting
confidence: 67%
“…Preliminary studies suggest that a single dose of between 50 and 125 mg of ceftriaxone per kg is adequate for the treatment of uncomplicated gonorrhea (4). In vitro susceptibility tests have shown that the minimal inhibitory concentration of ceftriaxone for P-lactamase-producing N. gonorrhoeae is approximately 0.01 ,ug/ml (10). These observations and the results of the current study suggest that ceftriaxone would be effective as a single-dose regimen against mixed infections with T. pallidum and ,1-lactamase-positive N. gonorrhoeae.…”
Section: Discussionsupporting
confidence: 67%
“…'9 20 Ceftriaxone is a new third generation cephalosporin that has been found to be active against both PPNG and non-PPNG strains.5 6 In the study published here the non-PPNG strains were more susceptible than PPNG strains to ceftriaxone, a finding noted previously by Thabaut et …”
Section: Discussionsupporting
confidence: 59%
“…Cephalothin, a first-generation cephalosporin that is 325-fold less effective than ceftriaxone against N. gonorrhoeae (89), permitted the growth of the Δngo1205 mutant, resulting in a final mutant OD 600 of 0.101, while the WT did not grow at all (File S1). However, the presence of moxalactam, a third-generation cephalosporin that is over 20-fold more effective than cephalothin (89), allowed the WT to grow to an OD 600 of 0.195, while the mutant achieved an OD 600 of 0.13 (File S1).…”
Section: Figmentioning
confidence: 99%